The woman's voice - Rodenburg, Patsy, 1953- (Bloomsbury Publishing, 2023)
"hy are women still often not properly listened to? Why are they sometimes perceived to be less interesting than they are? Why do women tend to rush when they speak? Why do many women feel the pressure to sound like girls when they speak? From one of the world's leading experts on voice work comes this book, which is a call to arms for women to reclaim the voice within through life and leadership. Arguing that power and voices are directly linked to breath, Rodenburg makes a case for the oppression of women in Western society over history having diminished our natural ability to breathe. She examines all of these questions, and many more, to decipher what lies at the heart of female empowerment when it comes to the voice. Combining elements of experience and practice from Patsy Rodenburg's prolific career, she interrogates Shakespeare's texts and presentation of female characters; develops the notion of rhetoric in relation to the female voice; and applies concepts explored in her previous books, such as the three circles of presence. Exploring the female voice through practical exercises and stories from the front line, as well as profoundly personal and formative experiences from her own life, the author defines the art of accessing the voice within and reclaiming the woman's right to speak. A highly personal call-to-action that clarifies the necessity of voice training in art and in life"--